1998
DOI: 10.1007/s11743-998-0016-4
|View full text |Cite
|
Sign up to set email alerts
|

Methyl ester propoxylates

Abstract: Insertion of propylene oxide into methyl esters is accomplished using a proprietary alkoxylation catalyst. The alkoxylation mechanism is believed to involve transesterification between the alkoxylated metal-alkoxide of the catalyst and the ester. Optimal alkoxylation conditions are discussed. The effect of inserting propylene oxide prior to ethoxylation on surface properties and foam performance is examined. JSD 1, 167-175 (1998). KEY WORDS:Fatty methyl ester propoxylates, methyl ester propoxylates, performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…It was proven that during ethoxylation of fatty methyl ester, EO was inserted selectively between the carbonyl carbon and the methoxy group (8). RCOOCH 3 + nCH 2 CH 2 O → RCO(OCH 2 CH 2 ) n OCH 3 [2] Substrate Adduct Ethoxylation product Propoxylation of fatty acid methyl esters was also reported in the literature (9). Earlier studies described the impact of methyl ester chain length, degree of unsaturation, and EO content on the physical properties and performance of methyl ester ethoxylates (7,10,11).…”
mentioning
confidence: 99%
“…It was proven that during ethoxylation of fatty methyl ester, EO was inserted selectively between the carbonyl carbon and the methoxy group (8). RCOOCH 3 + nCH 2 CH 2 O → RCO(OCH 2 CH 2 ) n OCH 3 [2] Substrate Adduct Ethoxylation product Propoxylation of fatty acid methyl esters was also reported in the literature (9). Earlier studies described the impact of methyl ester chain length, degree of unsaturation, and EO content on the physical properties and performance of methyl ester ethoxylates (7,10,11).…”
mentioning
confidence: 99%
“…Immediately thereafter, Lion Corporation (Tokyo, Japan) demonstrated that a magnesium/aluminum oxide-based catalyst also worked well (4). Since then, the development and use of ester alkoxylates have become an active area of research (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…Propoxylations and ethoxylations were performed with KOH and with an alkoxylation catalyst complex (called NOVEL ® II; CONDEA Vista Company, Houston, TX) that consists of a Ca/Al complex partially neutralized in an alcohol ethoxylate base (3). This Ca/Al alkoxide catalyst is an effective ethoxylation catalyst for producing "peaked" or "narrow-range" alcohol ethoxylates, and for the ethoxylation and propoxylation of esters (4)(5)(6)(7)(8)(9).…”
Section: Methodsmentioning
confidence: 99%